PUBLIC RECEPTION TOWARDS CSR PROGRAM AT PT BAKRIE SUMATERA PLANTATIONS TBK KISARAN - Sakinah, Khairani; Peranginangin, Indira Fatra Deni (International Journal of Cultural and Social Science, 2026)
This study examines public reception of the Corporate Social Responsibility (CSR) program of PT Bakrie Sumatera Plantations Tbk in Kisaran in 2025. The study is grounded in the view that CSR is not merely a form of corporate responsibility, but also a corporate communication practice through which the company encodes messages of care, legitimacy, and social closeness to surrounding communities. The novelty of this study lies in its use of Stuart Hall’s reception theory to analyze CSR in a plantation context, an area that remains underexplored in Indonesian corporate communication studies, particularly through a phenomenological lens. This research employed a qualitative phenomenological approach to capture the lived experiences of communities in interpreting the company’s CSR practices. Data were collected through in-depth interviews with 10 informants, supported by observation, documentation, and analysis of the company’s CSR report. The findings show that the CSR program was constructed as a corporate message through seven main sectors: education, health, religion, infrastructure and environment, social and disaster response, sports and youth, and economy. Public reception was predominantly situated in dominant-hegemonic and negotiated positions, indicating that community acceptance was generally positive but not entirely uncritical. These findings confirm that the meaning of CSR is shaped not only by program implementation, but also by how communities interpret, evaluate, and negotiate their experiences with the company.